The Impact of Interactivity, Perceived Effectiveness, Trust, and Experiential Marketing on Online Transportation Customer Loyalty - Ananda Sabil Hussein; Raditha Hapsari (Universitas Airlangga, 2021)
The purpose of this study is to examine the effect of interactivity, perceived effectiveness, trust, and experiential marketing on online transportation customers' loyalty in Indonesia. This study surveyed 264 online transportation customers. Purposive sampling was used to recruit respondents. Partial Least Squares analysis was used to analyze the data in three steps, including inner model analysis, outer model analysis, and hypothesis testing. The hypothesis testing supported seven of the nine hypotheses proposed. The findings of this study indicate that interaction is a significant predictor of online transportation consumer loyalty. The report also discusses the implications of the results and the direction for further research.